Delaminated layered double hydroxide nanosheets as an efficient vector for DNA delivery - Wang, J; Bao, W; Umar, A; Wang, Q; O'Hare, D; Wan, Y (American Scientific Publishers, 2016)
The performance of delaminated Mg–Al-lactate and Mg–Al-acetate layered double hydroxides (LDHs) nanosheets (Mg–Al-lactate-NS, Mg–Al-acetate-NS) as efficient vectors for DNA adsorption and delivery to 293T cells was investigated. Mg–Al-lactate and Mg–Al-acetate LDHs were delaminated into single layers in water and were characterized using XRD, SEM, TEM, and Zeta potential measurements. The salmon sperm DNA adsorption capacity of Mg–Al-lactate-NS and Mg–Al-acetate-NS were evaluated by varying the adsorbent dosage and contacting time, which suggested that Mg–Al-lactate-NS had much higher adsorption capacity (649.6 μg mg–1) than that of Mg–Al-acetate-NS (340.0 μg mg–1. XRD analysis indicated that after DNA adsorption the Mg–Al-lactate-NS-DNA bio-inorganic nanohybrid still stayed in an exfoliated form. Due to the difficulty in separating the Mg–Al-lactate-NS-DNA from solution, electrophoresis analysis was also applied to detect the free DNA in solution after adsorption. Cytotoxicity studies using 293T cells verified that Mg–Al-lactate-NS was less toxic than Mg–Al-acetate-NS as a smaller dose of this LDH was needed to deliver the same amount of salmon DNA to 293T cells. Cellular uptake and confocal imaging studies demonstrated that Mg–Al-lactate-NS was successful in transfection of ssDNA-FITC into 293T cells. However, the FITC-coupled single strand DNA was failed to be internalized into these cells. The excellent DNA adsorption and delivery capacities indicate that delaminated Mg–Al-lactate LDHs nanosheets are a better DNA vector than bulk phase LDH.